2010
DOI: 10.1177/104063871002200504
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Blood Selenium Concentrations of Goats in New York State

Abstract: Abstract. The goal of the current study was to determine the range of blood selenium concentrations in goats in New York State that were fed adequately supplemented diets. Blood samples from mature, juvenile, and neonatal goats from commercial farms, 2 dairy and 2 meat producers, were analyzed via graphite-furnace atomic absorption spectroscopy. Feed samples were analyzed by using inductively coupled argon plasma optical emission spectroscopy to confirm that dietary selenium concentrations were adequate. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…Similar levels of Se have been found in the blood of newborn calves and their mothers (Pavlata et al, 2004). In contrast to the obtained results herein, blood level of Se in the adult goats was significantly higher than those in neonate and juvenile goats (McComb et al, 2010). Also, the lower level of Se in the whole blood of goat kids has been reported in comparison with their mothers at first day of life (Misurova et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similar levels of Se have been found in the blood of newborn calves and their mothers (Pavlata et al, 2004). In contrast to the obtained results herein, blood level of Se in the adult goats was significantly higher than those in neonate and juvenile goats (McComb et al, 2010). Also, the lower level of Se in the whole blood of goat kids has been reported in comparison with their mothers at first day of life (Misurova et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…During milk suckling, Se level in the blood of neonates is influenced by the saturation of their mothers, as Se permeates placental and mammary barriers (Pavlata et al, 2004). In addition to sampling time, differences in location, breed, as well as nutritional status may contribute to contradictory results (McComb et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The results from this study showed that effective stabilization in goats. Graphite-furnace atomic absorption spectroscopy used to determine the concentration of heavy metals and also blood selenium concentrations of goats and cattle [ 208 , 209 ], lead and cadmium concentrations in goat, cow, sheep, and buffalo milks [ 210 ].…”
Section: Types Of Various Nanomaterials Used In Veterinary Medicinmentioning
confidence: 99%
“…The laboratory normal reference values for serum albumin, total proteins, AST, GGT, and CK were 24-44 g/l, 64-78 g/l, 58-350 IU/l, 5-89 IU/l and 20-194 IU/l, respectively. The threshold selenium concentration in whole blood below which goats were considered selenium deficient was 0.07 mg/dl (McComb et al, 2010).…”
Section: Biochemical Analysismentioning
confidence: 99%